PENGARUH KUALITAS PRODUK, KEMASAN, HARGA, DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA USAHA OTTITA PT. KARYA MEGA REZKY DI KECAMATAN TOPOYO - Khairunnisa Khairunnisa; Marhawati Marhawati; Agus Syam; Muhammad Jufri; Asmayanti Asmayanti (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The purpose of this study is to determine the influence of packaging, price, and social media on purchase decisions in the OttiTA business of PT. Karya Mega Rezky in Topoyo District. The independent variables in this study are product quality, packaging, price, and social media, while the dependent variable is the purchase decision. The population in this study includes all customers of PT. Karya Mega Rezky who have previously purchased or are interested in purchasing OttiTA products. The sample consisted of 96 respondents selected using the accidental sampling technique. Data were collected by distributing questionnaires to the respondents. The data analysis technique used was multiple linear regression analysis with the help of SPSS software. Based on the results of the analysis and discussion, it can be concluded that the Packaging variable (X2) has a partial influence on the dependent variable, namely Purchase Decision (Y). Meanwhile, the variables of Product Quality (X1), Price (X3), and Social Media (X4) do not have a partial influence on the dependent variable, Purchase Decision (Y). However, the variables Product Quality (X1), Packaging (X2), Price (X3), and Social Media (X4) collectively (simultaneously) have an influence on the dependent variable, Purchase Decision (Y).